Synergistic oxidation of levofloxacin in electro-peroxone system with enhanced in-situ N, P self-standing carbon cathode derived from Chlorella: In-situ H2O2 generation, peroxone activation and catalytic ozonation - Wei, Xingyue; Zhang, Hanmin; Cao, MengBo; Guo, Miao; Liu, Mengxuan (Journal of cleaner production, 2024)
An intrinsic N, P self-standing carbon block (NP SSCB) cathode prepared with Chlorella as a precursor was used to enhance the electro-peroxone (EP) process under acidic conditions through a temperature modulation strategy. The results exhibited that NP SSCB-800-EP had a synergistic effect on levofloxacin (LEV) degradation by 42.1% and produced in situ H2O2 up to 70 mg L−1. Quenching and EPR tests confirmed that ·OH, HO2·/O2·- and 1O2 were responsible for degradation of LEV. The quantitative results showed that EP process produced radicals in the order of 1O2> HO2·/O2·->·OH. X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculations under acidic conditions confirmed that pyridinic N, pyrrolic N, C-O-P and the defects were active sites for in-situ H2O2 production. Furthermore, pyridinic N, pyrrolic N and C-P-O groups contributed to the reaction of H2O2 with O3 to form HO2/O2·- and O3·- intermediates, free from overcoming the limitations associated with traditional HO2− production. Graphitic N and C3-PO were possible active sites for triggering the 1O2 and *Oad production. This work provides a new strategy for the preparation of self-standing carbon-based cathodes and achieves multiple functions of EP process under acidic conditions, presenting new insights into structure-functional relationships in carbon-based advanced oxidation processes. [Display omitted] •Intrinsic N, P self-standing carbon block was prepared using Chlorella as precursor.•NP SSCB-800 for EP process generated H2O2 and exhibited coupling effect of 42.1%.•·OH, HO2·/O2·- and 1O2 were the main active species for effective LEV degradation.•Pyridinic N, pyrrolic N, C-O-P and defects were active sites for H2O2 production.•Generation of HO2/O2·- and O3·- was attributed to pyridinic N, pyrrolic N and C-P-O.